2016
DOI: 10.1016/j.susc.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio calculations of surface phonons of the hydrogen-terminated Si(110)-(1 × 1) surface

Abstract: A first-principles study, using a linear-response approach based on the pseudopotential method and the generalized gradient approximation, has been made to examine the phonon spectrum of the hydrogen-terminated Si (110)- (1×1) surface. The calculated results compare very well with the results determined from a recent high-resolution electron-energy-loss spectroscopy measurement. In particular, the energy locations and polarization characteristics of the H-Si bond bending and H-Si stretching surface phonon mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
(51 reference statements)
1
1
0
Order By: Relevance
“…The characteristic extinction of specific spots for the p2mg symmetry is also common to D:Si(110) and H:Si(110). Note that the spots corresponding to (10), ð 10Þ, (30), and ð 30Þ are missing for all energies, in accordance with the two-dimensional extinction rule. 8,41,42)…”
Section: Confirmation Of D-terminated Si Surface Structuressupporting
confidence: 67%
See 1 more Smart Citation
“…The characteristic extinction of specific spots for the p2mg symmetry is also common to D:Si(110) and H:Si(110). Note that the spots corresponding to (10), ð 10Þ, (30), and ð 30Þ are missing for all energies, in accordance with the two-dimensional extinction rule. 8,41,42)…”
Section: Confirmation Of D-terminated Si Surface Structuressupporting
confidence: 67%
“…8) It was also found that the experimental data for surface phonons on H:Si(110) are useful for estimating the accuracy of first-principles calculations, such as quantum-mechanical calculations based on density functional theory (DFT), particularly in the frameworks of the local density approximation (LDA) 9) and generalized gradient approximation (GGA). 10) There are some inconsistencies between the results of the experiments and calculations, particularly in the vibrational frequencies of surface H atom modes. One possible approach to solving this problem is to study the phonon properties by examining the effects of atomic isotope replacement on the vibrational frequencies, both experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%